2008
DOI: 10.4238/vol7-3gmr404
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype description of two species of Hypostomus (Siluriformes, Loricariidae) of the Planalto da Bodoquena, Brazil

Abstract: ABStRACt. Hypostomus sp 3-Córrego Salobrinha NUP 4247 and Hypostomus sp 2-Rio Perdido NUP 4249, collected in the Planalto da Bodoquena, Paraguay River basin, Brazil, were characterized cytogenetically. Hypostomus sp 3-Córrego Salobrinha showed two modal numbers. This polymorphism consists of the presence of two extrachromosomes. It was not possible to define the diploid number in four specimens, where cell lineages had 2n = 83 and 2n = 84 chromosomes in one individual, and 2n = 82, 2n = 83 and 2n = 84 chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
5
40
0
1
Order By: Relevance
“…The standard C band observed in H. cf. plecostomus with a few conspicuous blocks on the long arm of the chromosome as well as on the short arms of other chromosomes, was also found in other species of the genus, such as H. affinis (Kavalco et al, 2004), H. nigromaculatus (Rubert et al, 2008), and H. cochliodon (Cereali et al, 2008). This corroborates the results of Artoni and Bertollo (1996) and Kavalco et al (2004), who reported that Hypostomus has relatively little constitutive heterochromatin.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The standard C band observed in H. cf. plecostomus with a few conspicuous blocks on the long arm of the chromosome as well as on the short arms of other chromosomes, was also found in other species of the genus, such as H. affinis (Kavalco et al, 2004), H. nigromaculatus (Rubert et al, 2008), and H. cochliodon (Cereali et al, 2008). This corroborates the results of Artoni and Bertollo (1996) and Kavalco et al (2004), who reported that Hypostomus has relatively little constitutive heterochromatin.…”
Section: Discussionsupporting
confidence: 84%
“…With the expansion of karyotypic data from this genus, its diversity has been further confirmed by different authors (Alves et al, 2006;Cereali et al, 2008;Rubert et al, 2011;Bueno et al, 2012Bueno et al, , 2013. In addition, hypotheses of phylogenetic relationships of the genus Hypostomus, based on taxonomic and molecular analysis (from mitochondrial DNA sequences) allowed some groupings with in this genus (Montoya-Burgos, 2003).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This genus is known for its wide degree of chromosome diversification (Artoni and Bertollo, 2001;Mendes-Neto et al, 2011;Bueno et al, 2012), with 2n ranging from 54 chromosomes in H. plecostomus (Muramoto et al, 1968) to 84 chromosomes in Hypostomus sp 2 (Cereali et al, 2008). Nevertheless, H. plecostomus could be a case of misidentification and could belong to another Loricariidae genus.…”
Section: Discussionmentioning
confidence: 99%
“…According to Reis et al (2006), this group is subdivided into six subfamilies: Loricariinae, Hypoptopomatinae, Hypostominae, Neoplecostominae, Lithogeninae, and Delturinae. In Hypostominae, the diploid number (2n) varies from 34 chromosomes in Ancistrus cuiabae (Mariotto et al, 2011) to 84 chromosomes in Hypostomus sp 2 (Cereali et al, 2008). Most cytogenetic studies show great variability in some chromosome features; however, molecular analyses, such as physical mapping of ribosomal genes, have been done for only a small number of species (Mariotto et al, 2011;Mendes-Neto et al, 2011;Rubert et al, 2011;Ziemniczak et al, 2012;Traldi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%